The Nomadic Lifestyle of the Blaan Tribe: A Phenomenological Study (American Journal of Interdisciplinary Research and Innovation, 2025)
This research aimed to investigate the nomadic lifestyle of the Blaan tribe, focusing on the life situation of the Blaan people in Davao Occidental. It explored the lived experiences of these nomadic people, their coping mechanisms, and their insights into engaging in a nomadic way of life. The study employed a qualitative research approach, specifically a phenomenological study design. A purposive sampling method was used to select participants. The results yielded four essential themes reflecting the lived experiences of the nomadic people: Limited Access to Basic Needs, Environmental Vulnerability, Limited Economic Opportunities, and Social Marginalization. Three themes were identified regarding the coping mechanisms employed by the nomadic people: Embrace Flexibility, Practice Mindfulness in All Ways, and Set Goals. Regarding the insights of the nomadic people, three themes emerged: Cultural Awareness, Adaptability, and Goal Setting. The findings highlight the need for policymakers and organizations to address the basic needs of the Blaan tribe, including food, water, shelter, and healthcare. Environmental protection efforts are crucial to support their nomadic lifestyle, while sustainable livelihood opportunities could improve their economic situation. To combat social marginalization, initiatives should focus on raising awareness and understanding of nomadic cultures.